Design, Fabrication and Test Performance of a Multi-Crop Grating Machine - Fadriquel, Orley (Romblon State University Research Journal, 2011)
The objective of this study is to design, fabricate and test the performance of the Multi-Crop Grating Machine. The multi-purpose grating machine was composed of four major components, namely: the hopper/feeding assembly, the grating and the power units, and the machine frame or support. The over-all dimension of the machine measured 300 mm in length, 300 mm in width and 1000 mm in height. In testing the machine, two types of grating blades, the coarse and the fine ones were used. The capacity of the machine in grating cassava using the coarse blade was 161 kg/hr and that for the fine blade was 107. While the grating of papaya requires the machine’s capacity of using the coarse blade for 71.43 kg/hr, that for the fine blade was 68.96. The grating of ginger showed that the capacity of the machine of using the coarse blade was 111.11 kg/hr, that for the fine blade was 80.54. To determine the viability of the machine economic analysis was made using the Internal Rate of Return. Results show that an investment for the multipurpose grating machine is profitable. The grating machine designed, fabricated and performance tested is found to be useful to the cassava, papaya and ginger processors because it lessen the time in grating the commodities.